Scale Matters: Temporality in the Perception of Affordances - Gastelum, Melina (Frontiers in Psychology, 2020)
In this paper I seek to unify enactive and ecological approaches to cognitive science by emphasizing the fact that both approaches view cognitive processes as being inherently temporally extended, my hypothesis is that characterizing the temporal scales in which perception of affordances occur, they can serve different purposes of explanation within the theories. Specifically, the paper brings together, on the one hand, Chemero’s (2009) dynamicist understanding of affordances, which he called affordances 2.0, with, on the other hand, a distinction originally made by Varela (1999), and later taken up by Shaun Gallagher (2011, 2017b), between three different timescales for understanding cognition: the elementary, the integrative, and the narrative. Varela’s threefold distinction was originally intended as a way of identifying phenomenological events as being causally coupled to specific cellular events happening within the nervous system. The central claim of the present paper is that affordances, likewise, should be understood in terms of these three different timescales. I show that these temporal scales can be a useful toolkit for explaining the perception and learning of affordances and at the same time unifying enactivism and ecological psychology claiming that affordances serve a different explanatory role depending on which time scale you consider them at. If you are interested in explaining the embodied assemblies that form the always changing sensoriomotor contingencies, then you see the elementary scale. If you’re interested in explaining perception at the integrative scale, then affordances are solicitations that get actualized and bear an umwelt at that same scale. The perception of affordances as such is constituted by the integration of this 2 first scales, and the experience of it can be characterized by the husserlian structure of experience with its intrinsic temporality. Finally, if you are interested in explaining change in the animal-environment system over developmental time, i.e. learning, then affordances are around what Chemero proposed and one should see at the narrative scale. But it is important to say that the three scales are always intertwined because learning and perception are ongoing processes that in many senses are impossible to separate.